Urban expansion and environmental sustainability: Analysis of land use/cover changes In Kasoa, Ghana - Liman Berikisu (University of Cape Coast, 2023)
The Environmental costs of rapid urbanization in African urban cities have gained great attention. Due to this, stakeholders and policymakers have placed much emphasis on the need to protect the environment. This study sought to assess the urban expansion of Kasoa and its effects on environmental sustainability. Using a mixed method approach and explanatory sequential design, the study used satellite data from 1985 to 2021. This was supplemented with qualitative data obtained from in-depth interviews conducted for key informants and focus group discussions for unit committee members. The findings showed that Kasoa has experienced high urbanization resulting in significant changes in the land use/land cover making the area vulnerable to high temperature and poor environmental stress. The study shows a tremendous change in all land use/ land cover classes studied and also a change in the average temperature. Though there are community-based initiatives to manage the pressures emanating from urbanization, however, implementation of these initiatives by land management institutions are often challenged by cultural and institutional bottlenecks. It is therefore recommended that traditional authorities of Kasoa in collaboration with various land management institutions should take steps to effectively coordinate, develop and implement appropriate by-laws and policies to strictly protect natural environment due to the rapid growing population and the accelerated rate of urbanization in Ghana.
xii,165p:,ill
Keywords: Environmental sustainability Ghana Kasoa Land use/ land use Urbanization